OPTIMALISASI ASET PASCA PON XVIII TAHUN 2012 DI PROVINSI RIAU âSTUDI PADA GELANGGANG REMAJA RIAUâ - , Yudha Patria, I Wayan Nuka Lantara, M.Si, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Optimization of asset utilization expected to contribute to the region, especially in terms of income Original area, which in turn is expected to increase the magnitude of Budget income and Expenditure area. From the data obtained in the Riau provincial government bodies, in particular the financial and Asset Management Areas that there is untapped potential assets optimally or idle assets included. This research aims to analyze asset utilization form policy priority goods belonging to the region, based on the decision making techniques with Analytic Network Process method (ANP) which was first developed by Thomas L. Saaty. This method capable of being is a new approach a method of qualitative. Itâs ability is to help us in making measurements and the synthesis of a number of factors in a network. In this research, used superdecision software which is able to help deliver the final value in the form of an already normalized eigenvector of limiting marix. The results showed that the Joint utilization of the highest priority, followed by occupying sequentially is BOT/BTO, self management system, rental and loan used. Keywords: analytic network process, optimization, superdecision, supermatrix